2022
DOI: 10.1144/qjegh2022-081
|View full text |Cite
|
Sign up to set email alerts
|

Natural and anthropogenic halite karst subsidence in north Cheshire, UK; comparison of Rostherne Mere, Melchett Mere, Tatton Mere and their surroundings

Abstract: Most of the north Cheshire - Knutsford Group - of meres (lakes) in the UK formed naturally by dissolution of Triassic halite after the Devensian glaciation. Anthropogenic brine extraction in the 19 th and 20 th Centuries produced further subsidence that enlarged some meres and formed the new lake of Melchett Mere. The characteristic features of three meres, Rostherne, Melchett and Tatton are compared here by historical surveys, maps, photographs and LiDAR interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Natural dissolution is sensitive to climatic changes, as it is to groundwater. Salt karst formation in the United Kingdom was studied by Cooper (2002), who suggested that the karsting was related to changes in the groundwater regime, for example, during the last (Devensian) glaciation (Serridge & Cooper, 2022). Essentially, when the ice sheet melted, groundwater level increased and enabled the circulation of freshwater through salt units interbedded with more permeable units of siltstone, mudstone and gypsum, allowing access of fresher groundwaters to new areas of halite.…”
Section: Introductionmentioning
confidence: 99%
“…Natural dissolution is sensitive to climatic changes, as it is to groundwater. Salt karst formation in the United Kingdom was studied by Cooper (2002), who suggested that the karsting was related to changes in the groundwater regime, for example, during the last (Devensian) glaciation (Serridge & Cooper, 2022). Essentially, when the ice sheet melted, groundwater level increased and enabled the circulation of freshwater through salt units interbedded with more permeable units of siltstone, mudstone and gypsum, allowing access of fresher groundwaters to new areas of halite.…”
Section: Introductionmentioning
confidence: 99%